FRI0362 Rapid Acquisition of Data on the Patient Perspective in Rheumatoid Arthrtis Through a Digital Portal. (9th June 2015) - Goel, N.; Cummins, G.; Downing, J.; van Tuyl, L.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by significant morbidity related to systemic and joint inflammation. With the availability of more targeted therapeutic approaches and the potential of disease remission, there is increased focus on utilizing patient reported outcomes to better evaluate RA treatment impact. Collecting such data efficiently, i.e., with relatively low cost and time expenditures, can be challenging. Social media is increasingly being used to obtain and share health information; it also provides novel opportunities for the conduct of outcomes research. MediGuard.org is a free online service that monitors the safety of prescription medicines, over-the-counter medicines, and health care supplements for over 2.6 million registered patients from the United States (US), United Kingdom (UK), France, Germany, Spain, and Australia. As part of the registration process, patients who enroll in the MediGuard.org service are able to provide consent to be contacted about future research opportunities which may include obtaining insights about their willingness to participate in a clinical trial as well as being pre-screened for clinical trial participation. A previous study has shown the validity of self-reported diagnosis information collected in a direct-to-patient approach. 1 Objectives: Implement digital direct-to-patient methodology to collect and incorporate data from RA patients in the US into the Outcome Measures in Rheumatoid Arthritis Clinical Trials (OMERACT) project to study the patient perspective on remission. Methods: MediGuard.org, a Quintiles' proprietary online patient community, includes approximately 40, 000 US RA patients. A random sample of these patients was contacted in December 2014 to obtain 50 responses to the OMERACT survey through a direct-to-patient digital communications platform. The survey was programmed in 6 hours. Patients did not receive any honoraria for survey completion. Results: The first survey was completed within seven minutes of initial digital outreach and the fiftieth within three hours. RA patients from 23 continental US states were represented. Of the 50 patients, 82% were female, mean age 54.8 years; male patients were older, mean age 61.7 years. RA diagnosis duration was 11.3 years average (range 1-40). Comorbidities including other autoimmune and musculoskeletal conditions, diabetes, cardiovascular disease, malignancies were reported by 70%; 76% reported synthetic (72%) and/or targeted (44%) disease-modifying antirheumatic drug use; 84% reported current RA disease activity. Additional usable data were obtained including those on education, employment, health insurance, income, remission state, health assessment questionnaire, and patient global for the project. Conclusions: The RA population accessed is similar in demographics to those reported in other databases from the US. 2, 3 This analysis documents the feasibility of gaining rapid and relevant responses from a representative community RA patient population regarding their perspective on RA remission through a digital direct-to-patient portal. References: Cascade E, et al. J Med Internet Res 2012;14:e137. Wolfe F, et al. Arthritis Rheum 1994;37: 481–494. Solomon DH, et al. Ann Rheum Dis 2010;69:1920–5. Disclosure of Interest: N. Goel Employee of: Quintiles, G. Cummins Employee of: Quintiles, J. Downing Employee of: Quintiles, L. van Tuyl: None declared